Impact of blue economy sectors using causality, correlation and panel data models - Rosa María Martínez-Vázquez; Juan Milán-García; Jose Ramos Pires Manso; Jaime De Pablo Valenciano (Frontiers in Marine Science, 2023)
IntroductionBlue economics research is a research field that is achieving more and more interest among international scientists. This study adds more knowledge as it aims to investigate the causal relationships between blue economic factors – living and non-living resources, ocean energy, port activities, shipbuilding and repair, maritime transport, coastal tourism, human development indicator, per capita income, fish capture, internal renewable water resources per capita, marine protected areas, greenhouse gas emissions and population density, all factors related to maritime activities – and the blue economy (BE) itself.MethodsIn order to reach these objectives, some special analytical and econometric methods are used. Among them the multivariate Granger causality theory, the correlation analysis and panel data techniques are employed. This set of methods helps us to study the complex set of relationships among the various factors related to the BE and their influence on per capita income (PCI) and economic growth. The data used to conduct this research were collected from the Eurostat, the E.U. statistical database. Several European countries and the span period 2010-2018 are used too.ResultsThe analysis showed evidence that per capita income is associated to other factors of the blue economy, that PCI (Granger) causes coastal tourism and population density, and that there are five other factors that positively influence PCI growth, namely, greenhouse gas emissions (GHG), maritime transport, nonliving resources and ports’ activities. This paper adds some new understandings to theory and calls the attention to society, in general, and the blue economics, in particular. For instance, if policymakers want to increase income per capita of these regions, they should take action on some variables such as human development indicator (HDI), greenhouse gas (GHG) emissions, living resources, maritime transport and ocean energy. The results reveal that blue economy is a good alternative to promote both economic growth and PCI.DiscussionThe concerns that make up the blue economy, such as ocean energy, port activities, ship building and repair, maritime transport, coastal tourism, HDI, maritime fish capture, marine protected areas, and GHG reductionare good factors to stimulate economic growth. Among these, the most influencing are maritime transport, living resources and the production of ocean energy. This study adds knowledge to theory, innovates in the methods and techniques used, in the results discovered, in its discussion, and in the mixture of blue economic factors, too. As far as we know, it is one of the first papers that fills this gap in the literature regarding the more and more important blue economy.